OTOMATISASI RISET KATA KUNCI DI MARKET PLACE - Mahasinul Akhlak, Muhammad Lutfi (STMIK BINA PATRIA, 2023)
Keyword research is marketing research of the 21st century. Success in choosing relevant and appropriate keywords will improve the visibility of online stores and selling products. Keyword research is needed on all marketplace platforms so it requires repetition of keyword research and takes quite a long time because existing media platforms have to be opened one by one. Therefore we need a tool or tools to conduct keyword research or keyword research that is effective and efficient by combining the process of searching for keywordsÂ in one tool. The scope of this research is to create tools based on the iMacros script for keyword searches on marketplace platforms, namely Shopee, Tokopedia, Lazada, JD ID, Bukalapak, and OLX. This study uses the Design Thingking development model, system analysis using SWOT and Feasibility analysis using TELOS (Engineering; Economic; Legal; Operational and Schedule). The results of the questionnaire for system users with questions referring to the TELOS feasibility study showed a feasibility level of 86.33%. This percentage illustrates that the system is feasible to use, easy to learn, easy to understand and effective in helping internet marketers in keyword research.Â Keywords: digital marketing, iMacros, design thinking, SWOT, TELOS.